Protocol for faecal microbiota transplantation in irritable bowel syndrome: the MISCEAT study – a randomised, double-blind cross-over study using mixed microbiota from healthy donors - Lenka Kramna; Ondrej Cinek; Jakub Hurych; Jiri Vejmelka; Lucie Hlinakova; Vladyslav Larionov; Michal Kulich; Pavel Kohout (BMJ Open)
Introduction Several studies have demonstrated dysbiosis in irritable bowel syndrome (IBS). Therefore, faecal microbiota transplantation, whose effect and safety have been proven in Clostridioides difficile infections, may hold promise in other conditions, including IBS. Our study will examine the effectiveness of stool transfer with artificially increased microbial diversity in IBS treatment.Methods and analysis A three-group, double-blind,randomised, cross-over, placebo-controlled study of two pairs of gut microbiota transfer will be conducted in 99 patients with diarrhoeal or mixed type of IBS. Patients aged 18–65 will be randomised into three equally sized groups: group A will first receive two enemas of study microbiota mixture (deep-frozen stored stool microbiota mixed from eight healthy donors); after 8 weeks, they will receive two enemas with placebo (autoclaved microbiota mixture), whereas group B will first receive placebo, then microbiota mixture. Finally, group C will receive placebos only. The IBS Severity Symptom Score (IBS-SSS) questionnaires will be collected at baseline and then at weeks 3, 5, 8, 11, 13, 32. Faecal bacteriome will be profiled before and regularly after interventions using 16S rDNA next-generation sequencing. Food records, dietary questionnaires, anthropometry, bioimpedance, biochemistry and haematology workup will be obtained at study visits during the follow-up period. The primary outcome is the change in the IBS-SSS between the baseline and 4 weeks after the intervention for each patient compared with placebo. Secondary outcomes are IBS-SSS at 2 weeks after the intervention and 32 weeks compared with placebo and changes in the number of loose stools, Bristol stool scale, abdominal pain and bloating, anthropometric parameters, psychological evaluation and the gut microbiome composition.Ethics and dissemination The study was approved by the Ethics Committee of Thomayer University Hospital, Czechia (G-18-26); study results will be published in peer-reviewed journals and presented at international conferences and patient group meetings.Trial registration number NCT04899869.